PEMBERDAYAAN NILAI-NILAI MASYARAKAT LOKAL SEBAGAI MODAL PEMBANGUNAN DEMOKRASI - Miswardi Miswardi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The demand for a democratic system of government in Indonesia is not only the demands of society but also constitutional demands. Therefore, regional autonomy is expected to be able to provide answers to both needs. Because the essence of local independence itself is a tangible form of the practice of democracy in society, in the way of giving autonomy to the region to advance its society democratically in various aspects of life, politics, social economy and culture, to answer the challenges in the era of globalization. Community involvement by empowering local community values is one surefire strategy in the process of democratization. Besides, bureaucratic reform is a necessity; therefore, a combination of allowing the benefits of local communities with the government bureaucracy system is an appropriate strategy for accelerating democratic development.